1996
DOI: 10.1097/00005344-199603000-00017
|View full text |Cite
|
Sign up to set email alerts
|

Attenuation of Reperfusion Arrhythmias by Selective Inhibition of Angiotensin-Converting Enzyme/Kininase II in the Ischemic Zone: Mediated by Endogenous Bradykinin?

Abstract: We studied the effects of angiotensin-converting enzyme (ACE)/kininase II inhibition selectively in the ischemic zone on reperfusion arrhythmias, and the role of bradykinin versus angiotensin II (produced locally in this zone) in modulating the severity of such arrhythmias. Isolated rat hearts (n = 12 per group) were subjected to independent perfusion of left and right coronary beds. The left coronary bed received the ACE/kininase II inhibitor ramiprilat, alone or in combination with either HOE140 (bradykinin … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
15
0

Year Published

1997
1997
2013
2013

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 26 publications
(16 citation statements)
references
References 28 publications
1
15
0
Order By: Relevance
“…Fig 2 summarizes the overall incidences of reperfusion-induced VT and VF. Consistent with our previous study, 32 the incidence of reperfusion-induced VF in the non-hypertrophied hearts in the SH control group subjected to 7 min of regional ischemia was 33%. AC increased the VF incidence to 92% (p<0.05 vs SH).…”
Section: Effects Of Ramipril On Heart Weightsupporting
confidence: 91%
See 1 more Smart Citation
“…Fig 2 summarizes the overall incidences of reperfusion-induced VT and VF. Consistent with our previous study, 32 the incidence of reperfusion-induced VF in the non-hypertrophied hearts in the SH control group subjected to 7 min of regional ischemia was 33%. AC increased the VF incidence to 92% (p<0.05 vs SH).…”
Section: Effects Of Ramipril On Heart Weightsupporting
confidence: 91%
“…32 Bradykinin B2 receptor antagonist HOE140 reversed that effect, indicating that antiarrhythmic effects are mediated through suppression of tissue ACE activity and a subsequent increase in endogenous bradykinin in ischemic myocardium. 32 It has been shown that bradykinin mediates the anti-hypertrophic effects of ramipril (at the same doses used in the present study) 33,40 and contributes to improvement of both metabolism and contractile function in hypertrophied myocardium. 41,42 That indicates that an increase in endogenous bradykinin may mediate the anti-arrhythmic effects of ramipril.…”
Section: Possible Mechanisms Mediating the Anti-arrhythmic Effects Ofmentioning
confidence: 97%
“…7 The infusion flow rate of the cardioplegic solution was recorded with the flow meter of the cardiopulmonary bypass machine. The rate was usually fixed between 200 and 300 ml/min.…”
Section: Measurement Of Coronary Vascular Resistancementioning
confidence: 99%
“…Angiotensin-converting enzyme inhibitors (ACE-Is) are well-established drugs for patients with hypertension, heart failure or diabetic microalbuminuria, with beneseveral animal models have shown that some of the cardioprotective effects of ACE-Is could be attributed to bradykinin [3]. Bradykinin stimulates NO production by endothelial cells, and may thereby help to ' correct ' endothelial dysfunction [4].…”
Section: Introductionmentioning
confidence: 99%